RELASI MAKNA ADJEKTIVA DAN NOMINA DALAM BAHASA MELAYU DIALEK SAMBAS - Muhardiasih, Yunita; Patriantoro, Patriantoro; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is focused on the semantic field, with the aim to describe the relation of meaning of adjectives and nouns in Malay Dialect Sambas (BMDS). The method used is descriptive method with qualitative research form. The data in this study are words that contain the relation of meaning adjectives and nouns in BMDS. Data source in this research is BMDS spoken by the speakers in Tebas Kuala Village, Tebas Sub-district, Sambas District. Technique of collecting data using skillful technique of advance, technique of fishing line, recording technique, and technique of note. Data collection tools used are notebooks, questionnaires, list of images, and recording devices. Data analysis technique used in this research is done through stages of describing data, analyzing data, and drawing conclusion. Based on the research results in BMDS there are synonyms, antonyms, homonyms, hyponim, and polysemics analyzed by adjective and adjectival word classes. There are twenty-two pairs of synonyms in this study that are divided into four types of synonyms, namely total and complete synonyms, synonyms not total but complete, synonyms total but not complete, and synonyms are not total and not complete. There are thirty pairs of antonyms in this study divided into five types of antonyms, namely absolute antonyms, antonym relations, polar antonyms, hierarchial antonyms, and multiple antonyms, four homonym five hyponim and six polysemic. Keywords: meaning relation, adjectives, and nouns.